Resolution and accommodation in the good constitution - Barber, NW (Cambridge University Press, 2022)
Those who ask what counts as a good constitution normally mean to ask a different question; that is, they mean to ask what counts as a good state. Most people do not care whether the wording of the constitution is elegant or crude, whether its structure is clear or complex, or whether it was produced by an elected convention or is an accident of history, and, generally, they are right not to care: what matters is the state that the constitution has produced. When the state is succeeding in its primary task of advancing its people’s well-being, the constitution is, by derivation, successful too. But whilst the constitution is defined by its relationship to the state – the assemblage of rules which creates that institution – it remains an instrument in its own right, distinct from the state which it creates. This chapter asks whether there are features of the constitution that can render it, in itself, good, separately from the state it constitutes. An answer to this question would need to show that the constitution, as a bare set of rules, can play a part in helping the state achieve its primary task, distinct from the construction and operation of the constitutional institutions it instantiates. Though a range of answers to this question could be given, this chapter will examine two contenders. Each of these provides ways in which the constitution might, in itself, serve to moderate disagreement within the community and help unite people behind the state.